Daniel's dinosaurs - Carmine, Mary (New York : Scholastic, 1990)
Daniel loves dinosaurs. In fact, all he ever thinks about are dinosaurs...until one day his mother takes him to the acquarium to see the sharks...
Keywords: Dinosaurs -- Fiction; Acquarium -- Fiction